The Concept of Leadership in Traditional and Modern - M. Yusup (Indonesian Journal of Education (INJOE), 2021)
Traditional leadership is a leadership born in the midst of a traditional society or a newly growing society. In traditional societies, the concept of leadership will emerge as an answer to the objective conditions they experience, when a problem in their life and their lives collide. This opinion is based on two theories, namely The Greatmen Theory and Trait Theory. Modern leadership is a leadership that takes place in active participation between leaders and followers. Through this participation, close relationships that influence each other are established between leaders and followers in order to achieve the desired goals together.